2013
DOI: 10.5152/tud.2013.020
|View full text |Cite
|
Sign up to set email alerts
|

Predictive preoperative factors of positivesurgical margins after robotic radical prostatectomy in low-risk prostate cancer

Abstract: Objective: Positive surgical margins after radical prostatectomy for localized prostate cancer is a powerful predictor of PSA recurrence. Clinical stage, Gleason score and preoperative PSA are predictive factors for positive surgical margin after radical prostatectomy. In this study, we aimed to identify preoperative factors affecting surgical margin positivity in low-risk prostate cancer after robotic radical prostatectomy (RARP). Material and methods:Between 2008 and 2011 ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Previously, the factors used to predict PSM after RP in PCa mainly relied on clinical information. Turan et al [ 33 ] identified that a positive core percentage of biopsy specimens, tPSA levels and the elapsed time between biopsy and surgery increased the risk of a PSM. Yang et al [ 11 ] reported that perineural invasion, higher biopsy Gleason scores and more positive cores in biopsy specimens were independent predictors of a PSM.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the factors used to predict PSM after RP in PCa mainly relied on clinical information. Turan et al [ 33 ] identified that a positive core percentage of biopsy specimens, tPSA levels and the elapsed time between biopsy and surgery increased the risk of a PSM. Yang et al [ 11 ] reported that perineural invasion, higher biopsy Gleason scores and more positive cores in biopsy specimens were independent predictors of a PSM.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of tumoral involvement in each biopsy core can be another predictor of inferior outcomes. 8 We were not able to assess this relationship in our study due to infrequent documentation of this variable.…”
Section: Discussionmentioning
confidence: 86%
“…There are several studies searching the role of other preoperative factors such as prostate volume, the number of positive cores, the rate of involvement in each core in low or intermediate group. 8 In this study, it was aimed to review the preoperative predictive factors for PSM in patients with low or intermediate risk prostate cancer who underwent retropubic radical prostatectomy in our institution.…”
mentioning
confidence: 99%